2021
DOI: 10.1136/bmjopen-2020-046371
|View full text |Cite
|
Sign up to set email alerts
|

Using a pragmatically adapted, low-cost contingency management intervention to promote heroin abstinence in individuals undergoing treatment for heroin use disorder in UK drug services (PRAISE): a cluster randomised trial

Abstract: IntroductionMost individuals treated for heroin use disorder receive opioid agonist treatment (OAT)(methadone or buprenorphine). However, OAT is associated with high attrition and persistent, occasional heroin use. There is some evidence for the effectiveness of contingency management (CM), a behavioural intervention involving modest financial incentives, in encouraging drug abstinence when applied adjunctively with OAT. UK drug services have a minimal track record of applying CM and limited resources to imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…We converted binary outcomes (provided as proportions), t values from between-samples t tests, odds ratios, and Cohen’s d values provided in the text to Hedges’ g s (Lipsey & Wilson, 2001). For studies with cluster randomized designs (Metrebian et al, 2021; Priebe et al, 2013), we adjusted Hedges’ g s using the intraclass correlation coefficients (ICC) provided in the text (Higgins, Eldridge, et al, 2020). For within-subject designs, we calculated Hedges’ g av using pretest and posttest means and SDs (or SEs) for continuous outcomes (Goulet-Pelletier & Cousineau, 2018; Lakens, 2013) and converted binary outcomes (provided as proportions) to Hedges’ g av (Borenstein et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…We converted binary outcomes (provided as proportions), t values from between-samples t tests, odds ratios, and Cohen’s d values provided in the text to Hedges’ g s (Lipsey & Wilson, 2001). For studies with cluster randomized designs (Metrebian et al, 2021; Priebe et al, 2013), we adjusted Hedges’ g s using the intraclass correlation coefficients (ICC) provided in the text (Higgins, Eldridge, et al, 2020). For within-subject designs, we calculated Hedges’ g av using pretest and posttest means and SDs (or SEs) for continuous outcomes (Goulet-Pelletier & Cousineau, 2018; Lakens, 2013) and converted binary outcomes (provided as proportions) to Hedges’ g av (Borenstein et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Our clinical report (9) found that CM in addition to TAU (OAT plus 12 weekly specialist drug and alcohol keyworker sessions) only achieved a statistically significant difference in heroin use compared to TAU alone in the CM Attendance group at the 12-week follow-up, which was not sustained at the 24-week follow-up after incentives were withdrawn. CM targeted at attendance and abstinence (CM Abstinence) failed to achieve statistically significant reductions in heroin use compared to TAU at either follow-up.…”
Section: Discussionmentioning
confidence: 69%
“…Each cluster was randomly assigned to additionally provide either: i) positive reinforcement in the form of a £10 voucher given to participants at each weekly appointment for both on-time attendance and abstinence from opiates using an instant cup test (CM Abstinence group); ii) positive reinforcement in the form of a £10 voucher given at each weekly appointment for on-time attendance only (CM Attendance group); or no CM. The main clinical results (9) and design details (10) are reported elsewhere.…”
Section: Interventionsmentioning
confidence: 99%
“…While buprenorphine and buprenorphine–naloxone prescription have been associated with higher rates of discontinuation versus methadone prescription [ 52 ], others have reported contrasting findings [ 55 ] and large‐scale studies are being implemented to guide clinical practice [ 24 , 56 , 57 ]. Interventions to improve medication regimen choice through better assessment of symptoms have been proposed [ 58 ], and strategies to increase retention through counselling, therapeutic drug monitoring [ 59 ] and contingency management are being tested [ 59 , 60 ] and have shown promise [ 61 ]. Providing stable housing and employment opportunities support the recovery process beyond OAT retention through promoting personal satisfaction and social integration.…”
Section: Discussionmentioning
confidence: 99%